Strategic Approaches to Carbon Footprint Reduction in Logistics Operations - Marjan, Yakuttinah; Faisal, Ahmad (Logistica : Journal of Logistic and Transportation, 2025)
The logistics sector plays a pivotal role in global carbon emissions, accounting for a substantial share of greenhouse gases and making it a critical focus for sustainability transitions. This narrative review examines strategies for carbon footprint reduction in logistics by synthesizing evidence from Scopus, Web of Science, and Google Scholar. Literature was screened through inclusion and exclusion criteria and analyzed thematically. Five core strategies were identified: transportation and routing optimization, green supply chain management, renewable energy and digital decarbonization technologies, cold chain and food supply efficiency, and corporate mobility integration. Optimization algorithms such as Ant Colony Optimization and Vehicle Routing Problem models reduce emissions and operational costs. Green supply chain practices deliver up to 30% emission reductions while enhancing corporate performance. Renewable energy and IoT-enabled systems contribute to energy efficiency, while cold chain improvements reduce food waste. Corporate mobility strategies align organizational policies with sustainability goals, offering long-term competitive advantages. Despite these advances, systemic barriers remain, including inconsistent policies, organizational resistance, and high investment costs. Addressing these challenges calls for integrated, multi-level approaches to accelerate the transition toward low-carbon operations.